The Antibacterial Effect of Lerak Fruit Decoction (Sapindus rarak DC) on the Growth of Streptococcus mutans as an Alternative Cavity Cleanser Material (In Vitro) - Nevi Yanti; Fitri Yunita Batubara; Cut Nurliza; Bryan Julio Hasim (TALENTA, 2024)
Cavity cleanser is needed to remove smear layers and eliminate microbes. In this context, lerak fruit decoction (Sapindus rarak DC) is an important natural material used as an alternative to 2% CHX. The fruit effectively removes smear layers, possesses antimicrobial properties, and shows low surface tension. Therefore, this research aims to analyze the effectiveness of lerak fruit decoction as an alternative material for cavity cleanser material. The laboratory experiment commences with boiling 100 grams of lerak fruit in 100 ml of distilled water to obtain MIC and MBC values with the Dilution and Drop Plates Miles Misra method. The results of ANOVA and LSD tests show that lerak fruit decoction has antibacterial effect with MIC and MBC values of 12.5% and 25%, respectively. This research serves as the foundation for further investigations into lerak fruit decoction, considering the availability, biocompatibility, affordability, and ease of processing. Moreover, it can be concluded that 25% lerak fruit decoction has similar antibacterial ability to 2% CHX against Streptococcus mutans.